2009
DOI: 10.1159/000264686
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Equivalence Trial of Intensive and Semiannual Applications of Fluoride Varnish in the Primary Dentition

Abstract: For children in the primary dentition with high caries prevalence the standard semiannual application of fluoride varnish may not be successful in preventing tooth decay. Oftentimes this population is mobile and does not receive consistent preventive care. This trial tested whether an intensive fluoride 5% sodium varnish regimen (three applications/2 weeks) applied annually has an equivalent effect on caries progression in the primary dentition compared to single applications applied semiannually. This study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
1
20
0
2
Order By: Relevance
“…Limited evidence found no clear effect on caries increment between performing a single fluoride varnish once every 6 months versus once a year 13 or between a single application every 6 months versus multiple applications once a year or every 6 months. 14,15 Suggestions for Practice Regarding the I Statement…”
Section: Timing and Dosage Of Preventive Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited evidence found no clear effect on caries increment between performing a single fluoride varnish once every 6 months versus once a year 13 or between a single application every 6 months versus multiple applications once a year or every 6 months. 14,15 Suggestions for Practice Regarding the I Statement…”
Section: Timing and Dosage Of Preventive Interventionsmentioning
confidence: 99%
“…8,9 Three fair-quality studies evaluated the effect of frequency of fluoride varnish application on caries outcomes. [13][14][15] Two found that multiple fluoride varnish applications within a 2-week period were associated with no statistically significant differences in caries incidence versus a 6-month application schedule. 14,15 One trial found no statistically significant difference in caries rates for once-versus twice-yearly varnish application.…”
Section: Fluoride Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…These combinations provide preventive and antimicrobial properties against Mutans streptococci and Lactobacilli with as effective as an anti-caries agent without staining the porous dental tissues black, as does silver diamine fluoride (SDF) and amalgam. NSF is low in cost substance and available as a yellow solution that proves to be stable for 3 years (64). SDF has been shown to be more effective than fluoride varnish (63).…”
Section: Preventionmentioning
confidence: 99%
“…Baseado nesse princípio, alguns estudos em Odontologia têm sido delineados utilizando um grupo controle em que o placebo seja utilizado (12,28,29). Nem sempre os produtos odontológicos a serem testados permitem que seus placebos os reproduzam em todas as características, que seria necessário para um placebo ideal (24).…”
Section: Introductionunclassified